The effect of social comparison on debt taking: Experimental evidence - Antonia Grohmann; Melanie Koch (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
A number of studies show that there is a link between social comparison and high levels of household debt. However, the exact mechanisms behind this link are not yet well understood. In this paper, we perform a lab experiment designed to study the eff ects of social image concerns and peer information on consumption choices that can be financed through debt taking. We find that having to announce one's consumption decision publicly leads to leaving money on the table, which is the opposite of what we expected. Being informed about other participants' choices leads to conformity in choices between participants.
Keywords: D14; D12; D91; 330; Household Finance; Lab experiment; Social Comparison; Peer Effects